Rekeang as a Concept of Sustainability in the House of the Society of Karampuang: Redefining Granary - Nita Dwi Estika; Feni Kurniati; Achmad Syaiful Lathif (International Journal of Built Environment and Scientific Research, 2020)
Whether granaries in traditional communities have survived or being neglected due to modern progress has been widely discussed. However, the discussion remains fragmented and isolated solely on the granary itself, without considering the possibility of its more comprehensive relations. This paper aims to delve into the granary roles in Karampuang, a traditional village in South Sulawesi, to understand how the granary (in the local term 'rekeang') functions and sustains while facing modernization. The inquiry focuses on the interactions between rekeang and farming products, which further results in an understanding of interrelationships between rekeang and its surroundings: 1) domestic spaces, 2) family house units, and 3) with other rekeangs. Each relationship reveals that rekeang has a vital role, besides storing up farming products, it also serves as the key to sustaining the community, especially in cultural and ecological contexts. In the end, the paper proposes a critical insight of 'granary as a network,' which might provide an alternative approach to achieve sustainable development in traditional environments.